Quantitative 18F-fluorodeoxyglucose positron emission tomography/computed tomography to assess pulmonary inflammation in COPD. Issue 3 (31st August 2021) - Vass, Laurence; Fisk, Marie; Cheriyan, Joseph; Mohan, Divya; Forman, Julia; Oseni, Adelola; Devaraj, Anand; Mäki-Petäjä, Kaisa M.; McEniery, Carmel M.; Fuld, Jonathan; Hopkinson, Nicholas S.; Lomas, David A.; et al.
Rationale: COPD and smoking are characterised by pulmonary inflammation. 18 F-fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) imaging may improve knowledge of pulmonary inflammation in COPD patients and aid early development of novel therapies as an imaging biomarker. Objectives: To evaluate pulmonary inflammation, assessed by FDG uptake, in whole and regional lung in "usual" (smoking-related) COPD patients, alpha-1 antitrypsin deficiency (α1 ATD) COPD patients, smokers without COPD and never-smokers using FDG PET/CT. Secondly, to explore cross-sectional associations between FDG PET/CT and systemic inflammatory markers in COPD patients and repeatability of the technique in COPD patients. Methods: Data from two imaging studies were evaluated. Pulmonary FDG uptake (normalised Ki ; nKi ) was measured by Patlak graphical analysis in four subject groups: 84 COPD patients, 11 α1 ATD-COPD patients, 12 smokers and 10 never-smokers. Within the COPD group, associations between nKi and systemic markers of inflammation were assessed. Repeatability was evaluated in 32 COPD patients comparing nKi values at baseline and at 4-month follow-up. Results: COPD patients, α1 ATD-COPD patients and smokers had increased whole lung FDG uptake (nKi ) compared with never-smokers (0.0037±0.001, 0.0040±0.001, 0.0040±0.001 versus 0.0028±0.001 mL·cm −3 ·min −1, respectively, p<0.05 for all). Similar results were observed in upper and middle lung regions. In COPD participants, plasma fibrinogen was associated with whole lung nKi (β=0.30, p=0.02) in multivariate analysis adjusted for current smoking, forced expiratory volume in 1 s % predicted, systemic neutrophils and C-reactive protein levels. Mean percentage difference in nKi between the baseline and follow-up was 3.2%, and the within subject coefficient of variability was 7.7%. Conclusions: FDG PET/CT has potential as a noninvasive tool to enable whole lung and regional quantification of FDG uptake to assess smoking- and COPD-related pulmonary inflammation. FDG PET/CT has potential utility to noninvasively evaluate pulmonary inflammation in COPD. Pulmonary FDG uptake is increased in COPD patients, positively associated with systemic inflammatory markers and shows low inter-occasion variability. https://bit.ly/3dELYAW